(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The world economy fast paces with developed is going of our country this development to the process join with him together develop and change from the head in forgiveness our country big strength and high to development have to be for country socio-economic in his life achievement and disadvantages, opportunity and conditions out of consideration did not leave without of development intended degree and to the results reach ways find, of them maximum level use of this for necessary has been all measures done increase